„Poznański Czerwiec 1956”. Historia wydania książki - Kledzik, Bronisław (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The author remembers the initiatives taken in 1981 to celebrate the twenty fifth anniversary of Poznań 1956 protest.